2020
DOI: 10.21203/rs.3.rs-32822/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SOX9 in prostate cancer is upregulated by cancer-associated fibroblasts to promote tumor progression through HGF/c-Met-FRA1 signaling

Abstract: Background Previous studies have demonstrated that transcription factor SOX9 which was reactivated in prostate cancer (Pca) and promoted tumor growth was a poor prognostic biomarker for Pca. Nevertheless, the regulatory mechanism underlying SOX9 upregulation in Pca still remains unclear. Several cytokines widely distributed in the tumor microenvironment (TME) have been reported to be involved in the regulation of SOX9, suggesting that cancer-associated fibroblasts (CAFs), one of the main sources of secreted f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Changes in the microenvironment can activate and maintain HIF, which, in turn, stimulates the transcription of related genes involved in metabolic reprogramming and PDAC generation, invasion, metastasis, and angiogenesis 2 , 3 . Meanwhile, cancer-associated fibroblasts (CAFs), a kind of activated fibroblast, are present in practically all solid tumors, especially in pancreatic, breast, and prostate cancers 4 6 . CAFs play a critical role in the formation and progression of a variety of cancers since they are one of the most important components of the tumor microenvironment (TME).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the microenvironment can activate and maintain HIF, which, in turn, stimulates the transcription of related genes involved in metabolic reprogramming and PDAC generation, invasion, metastasis, and angiogenesis 2 , 3 . Meanwhile, cancer-associated fibroblasts (CAFs), a kind of activated fibroblast, are present in practically all solid tumors, especially in pancreatic, breast, and prostate cancers 4 6 . CAFs play a critical role in the formation and progression of a variety of cancers since they are one of the most important components of the tumor microenvironment (TME).…”
Section: Introductionmentioning
confidence: 99%
“…SOX9, a member of the family of SOX (SRY-related highmobility group box) genes, exerts regulatory functions in multiple organs development, cell-fate decision, and differentiation (8). Accumulating studies have demonstrated that SOX9 is also involved in the development of multiple cancers, including gastrointestinal, breast, brain, urological, and lung cancers and others (9)(10)(11)(12)(13). Collectively, SOX9 plays critical roles in tumor development and progression, including tumor initiation, tumor microenvironment regulation, metastasis, and drug resistance (14,15).…”
Section: Introductionmentioning
confidence: 99%